THE INSULA: ISLAND OF REIL. Issue 11 (14th October 2015) - Wynford-Thomas, Ray; Powell, Rob
Abstract : Just as 'no man is an island', despite its misleading name, the insula is not an island. Sitting deeply within the cerebrum, the insular cortex and its connections play an important role in both normal brain function and seizure generation. Stimulating specific areas of the insula can produce somatosensory, viscerosensory, somatomotor and visceroautonomic symptoms, as well as effects on speech processing and pain. Insular onset seizures are rare, but may mimic both temporal and extra-temporal epilepsy and if not recognised, may lead to failure of epilepsy surgery. We therefore highlight the semiology of insular epilepsy by discussing three cases with different auras. Insular onset seizures can broadly be divided into three main types both anatomically and according to seizure semiology: 1. Seizures originating in the antero-inferior insula present with laryngeal constriction, along with visceral and gustatory auras (similar to those originating in medial temporal structures). 2. Antero-superior onset seizures can have a silent onset, but tend to propagate rapidly to motor areas causing focal motor or hypermotor seizures. 3. Seizures originating in the posterior insula present with contralateral sensory symptoms.